Relationship between swallow‐specific quality of life and fiber‐optic endoscopic evaluation of swallowing findings in patients with head and neck cancer. (23rd December 2015) - Florie, Michelle; Baijens, Laura; Kremer, Bernd; Kross, Kenneth; Lacko, Martin; Verhees, Femke; Winkens, Bjorn
Abstract: Background: The purpose of this study was to determine the relationship between swallow‐specific quality of life (QOL) using the MD Anderson Dysphagia Inventory (MDADI) and the swallowing function using a standardized fiber‐optic endoscopic evaluation of swallowing (FEES) protocol in patients with dysphagia with head and neck cancer. Methods: Sixty‐three patients with dysphagia and head and neck cancer were enrolled in the study. Patients completed the MDADI questionnaire and underwent a standardized FEES examination. Ordinal FEES variables were measured. Descriptive statistics and 1‐way analysis of variance tests were carried out. Results: For all FEES variables, the observer agreement level was sufficient (kappa ≥0.7).These preliminary results show statistically significant mean differences of MDADI subscales between the ordinal scale levels for several FEES variables. Conclusion: The MDADI questionnaire can be used to assess the impact of dysphagia on the patients' health‐related QOL. Despite clear trends, it remains unclear if the MDADI questionnaire can be used as an indicator for the severity of oropharyngeal dysphagia. © 2015 Wiley Periodicals, Inc. Head Neck 38 : E1848–E1856, 2016